Efficacy & Biochemical Evaluation of Pharmaceutical Optimized Valsartan 80mg (F-3) with Essential Hypertension (Medical Forum Monthly, 2024)
Objective: The objective of this double-blind, comparative study evaluating efficacy and biochemical effects of optimized Valsartan 80mg (F-3) as monotherapy in adult patient with essential hypertension.Study Design. Double-blind, comparative studyPlace and Duration of Study: This study was conducted at the Department of Biochemistry, University of Karachi from January 2011 to September 2011.Materials and Methods: This was multicenter randomized, double-blind, comparative study. Patients were randomized to receive once Valsartan (F-3) daily for 8 weeks and at the end of study efficacy and biochemical evaluation was done.Results: The patients treated with optimized Valsartan 80mg (F-3) alone, blood pressure reduction was lower, although significant; reaching values of 140.9 ± 11.3 / m88.9 ± 5.5 mmHg (p < 0.05 versus Placebo) by the end of eight weeks of treatment. . No significant variation of blood glucose was observed and different parameters of lipid profile were also observed during the eight weeks of treatment with antihypertensive regimen used. Thus, the drug regimens used may be considered neutral as regards glucose and plasma lipid metabolism profile because drug used at low doses.Conclusion: We can suggest that the high antihypertensive efficacy, good tolerability and no biochemical effects of the optimized Valsartan 80mg (F-3) it is an excellent option for the treatment of hypertension in a wide range of hypertensive patients, with a high potential to reduce cardiovascular risks